Telemedicine for the Self-Management of Type 2 Diabetes: A Literature Review - Masepia, Bunjamin Dante; Isworo, Atyanti (Jurnal Keperawatan Soedirman, 2021)
The COVID-19 pandemic is an obstacle that prevents type 2 diabetes sufferers from visiting primary health services. Telemedicine is a virtual health service which helps caregivers and clients to meet virtually. Telemedicine is capable of helping sufferers in the form of self-management. The purpose of this study is to determine the effectiveness of telemedicine for the self-management of type 2 diabetes patient. This study uses a literature review design. Primary studies to be included in this review were searched from Pubmed electronic database. The inclusion criteria of studies were: published in the last 5 years in English-language journals, used randomized control trial design, had population aged > 18 years with type-2 diabetes, and used telemedicine. The exclusion criterion was comparing two or more telemedicine applications. A total of 11 studies was included in the review. Seven out of eleven studies showed a significant reduction in HbA1c in the intervention group compared to the control group. Another result is a change in diet by consuming more fruits and whole grains and an increase in knowledge, skills and ability to control blood sugar. This review concluded that telemedicine is effective in the self-management of type 2 diabetes patient. Health care professionals can use telemedicine as an alternative to improve self-management of type 2 diabetes patient.